Effects of Whole‐Body Vibration Therapy on Distal Tibial Myotendinous Density and Volume: A Randomized Controlled Trial in Postmenopausal Women. (13th December 2018) - Boggild, Miranda K; Tomlinson, George; Erlandson, Marta C; Szabo, Eva; Giangregorio, Lora M; Craven, B Catharine; Slatkovska, Lubomira; Alibhai, Shabbir MH; Cheung, Angela M
ABSTRACT: Whole‐body vibration (WBV) therapy has been proposed as a therapy to reduce sarcopenia and improve muscle strength. The purpose of this study was to explore whether 12 months of WBV therapy increases myotendinous density and volume of the distal tibia as measured by HR‐pQCT in postmenopausal women in a parallel group, randomized controlled trial with 1:1:1 allocation to three arms. Postmenopausal women ( N = 202) with low hip BMD were randomized to 20 min daily of 0.3 g 30‐Hz WBV therapy, 0.3 g 90‐Hz WBV therapy using the Juvent platform (Juvent, Somerset, NJ, USA), or no WBV. The main outcome measure was myotendinous density (HU) and volume (mm 3 ) at the distal tibia measured at baseline and 12 months with HR‐pQCT. There were no significant effects on myotendinous density or volume at the distal tibia after 12 months of daily 30‐ or 90‐Hz WBV therapy compared with no WBV therapy. Mean change (SD) in myotendinous density from baseline was 4.6 (5.7) HU in the 30‐Hz WBV group, 3.9 (6.1) HU in the 90‐Hz WBV group, and 3.9 (5.4) HU in the control group ( p = 0.70). Mean change (SD) in myotendinous volume from baseline was −7 (503) mm 3 in the 30‐Hz WBV group, 111 (615) mm 3 in the 90‐Hz WBV group, and 35 (615) mm 3 in the control group ( p = 0.50). In conclusion, WBV therapy at 30‐ or 90‐Hz for 12 months had no significant effects on myotendinous density or volume at the distal tibia as measured by HR‐pQCT in postmenopausal women. © 2018 The Authors. JBMR Plus Published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.